Photochromic photography with hackmanite obtained by large-scale synthesis - Vuori Sami; Byron Hannah; Norrbo Isabella; Tuomisto Minnea; Lastusaari Mika (Korean Society of Industrial and Engineering Chemistry, 2025)
Hackmanite (Na8Al6Si6O24(Cl,S)2) is an intelligent mineral that changes its color from white to pink upon exposure to UV radiation, X-rays, or gamma radiation and reverts to white by exposure to visible light or heat. This reversible photochromism can be used in e.g. solar UV indexing, X-ray imaging, gamma radiation detection, and intelligent clothing. Hackmanite is conventionally synthesized in a laboratory with yields measured in grams, which is low in an industrial aspect when considering the material’s vast application portfolio. In this work, we show that it is possible to produce hackmanite in an industrial scale with the final product yield of up to 1 kg marking a significant advance towards the commercial use of hackmanite. We also show yet another novel application invention: a photochromic photographic film that can be reused indefinitely due to hackmanite’s coloration ability that does not weaken with repeated use.